1979
DOI: 10.1093/clinchem/25.5.705
|View full text |Cite
|
Sign up to set email alerts
|

Elemental composition of platelets. Part II. Water content of normal human platelets and measurements of their concentrations of Cu, Fe, K, and Zn by neutron activation analysis.

Abstract: We determined the elements Cu, Fe, K, and Zn in normal human platelets by neutron activation analysis. The platelets were obtained from seven donors and treated as described in Part I. The elemental composition is expressed on a wet-weight basis for plasma-free platelets. The following results were obtained (+/- values are 1 SD); "Pure" platelets: trapped plasma = 378 +/- 35 mg/g, water content = 715 +/- 15 mg/g, mean weight of the single platelet (by two different methods) = 9.9 +/- 1.1 pg and 11.2 +/- 1.7 pg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Therefore, about half of the Zn 2+ in platelets is released when platelets are activated. This represents ~ 5 µM Zn 2+ released by the equivalent number of platelets normally in blood, consistent with previous reports (24,25). Therefore, when platelets are activated and aggregate at the site of injury, the local concentration of Zn 2+ can increase above the 10-20 µM reported in platelet-poor plasma (6)(7)(8).…”
Section: Quantification Of Zn 2+ In Platelets and Platelet Releasatesupporting
confidence: 90%
“…Therefore, about half of the Zn 2+ in platelets is released when platelets are activated. This represents ~ 5 µM Zn 2+ released by the equivalent number of platelets normally in blood, consistent with previous reports (24,25). Therefore, when platelets are activated and aggregate at the site of injury, the local concentration of Zn 2+ can increase above the 10-20 µM reported in platelet-poor plasma (6)(7)(8).…”
Section: Quantification Of Zn 2+ In Platelets and Platelet Releasatesupporting
confidence: 90%
“…They found iron deficiency anemia in women caused arachidonic acid induced platelet dysfunction through iron-containing enzymes may give rise to increased menstrual blood loss, which can be reversed through iron repletion. Kiem et al 12 showed that iron is present in platelets in a concentration of approximately 12.28 µg/g, further supporting the hypothesis of Karpatkin and colleagues 13 that iron may have a functional role in controlling platelet production.…”
Section: Discussionmentioning
confidence: 64%
“…In further support of this conclusion, it has been shown that APC inactivates factor Va much more efficiently on artificial phospholipid membranes or endothelial cells than on platelets (38). Cu 2+ ions, which are also found in platelets, may contribute to such effect (39).…”
Section: Discussionmentioning
confidence: 78%